PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIFE DUA TINGGAL ( TWO STAY TWO STRAY ) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 40 PEKANBARU - Sri astuti Sri astuti; Eddy Noviana Eddy Noviana; Otang kurniaman Otang kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak: Backgroun in this research were teachers still use the lecture method and assignments are give students soas to make the students guickly bored with the result that less than the maximum.It is visible symptoms on student attitudes, play in learning and less responds to a question or an explanation of from the teacher. Fot it needs to be done research of learning model two stay two stray. In this leaning students learning with two stay two stray in place group form of this research is classroom action research (PTK). This research aims to improve learning outcomes IPS of cassl IV elementary school 40 pekanbaru. The data obtained is guantitative data. The formulation of problem is”is the implementation cooperative learning model two stay two stray can improve learning outcomes IPS of class IV elementary school 40 Pekanbaru?. Quantitative data such as test results of student outcomes through repetition cycle. Increase in outcomes IPS students of the average value of basic score is 63,5 increased to 79,82 at the end of repetition cycle I with a large increased is 25,70%. The next value of average basic score 63,5 increased to 83,93 at the end of repetition cycle II with a large  increased is 32,17%. And the next value of the average basic score 63,5 increased to 89,64 at the and repetition cycle III with a large increased is 41,16%. Key word: Two  Stay Two Stray , Learning Outcomes